Template-directed synthesis of pi-conjugated porphyrin [2]rotaxanes and a [4]catenane based on a six-porphyrin nanoring - Langton, M; Matichak, J; Thompson, A; Anderson, H (2011)
[2]Rotaxanes consisting of butadiyne-linked porphyrin dimers threaded through a phenanthroline-containing macrocycle, can be synthesised by an active-metal template directed copper-mediated Glaser coupling, in yields of up to 61%, without requiring a large excess of the macrocycle. The crystal structure of one of these rotaxanes confirms that the macrocycle is clasped around the centre of the porphyrin dimer. A radial hexa-pyridyl template was used to convert the alkyne-terminated [2]rotaxane into a [4]catenane cyclic porphyrin hexamer in 62% yield, via palladium-catalysed Glaser coupling. The related [7]catenane porphyrin dodecamer complex was also isolated as a by-product of this cyclisation, in 6% yield. These results illustrate the scope of template-directed synthesis for creating complex interlocked structures directly from simple starting materials. © The Royal Society of Chemistry 2011.